Attention K-Mart shoppers: Blowout on aisle 7! - Griffith, Leslie C. (2009)
The mechanistic basis of arousal is controversial. A new study in Drosophila, where dopamine has been shown to be involved in several types of attentional processes, demonstrates that it independently regulates distinct types of arousal. These data provide evidence for molecularly convergent but anatomically divergent, task-specific, arousal circuits.